Halal and Tayyib? Islamic views on Genetically Modified Food(GMF) - Bouzenita, Anke Sandra (2010)
Genetically Modified Food(GMF) has become a reality worldwide. Concerns as to its health innocuousness, ecological and economic implications have been raised vehemently. With regard to the particular Islamic exigencies on nutrition (the halal status), Islamic deliberations on the permissibility of GMF are to be expected, particularly in case prohibited organisms are involved 'in the making'. Muslim's concerns, however, transcend the mere legalistic concern of food purity. The presentation will consider Islamic views on the halal status as well as the wholesomeness of GMFs in comparison to 'conventional' food on a holistic basis.